(3eQcR GdJMce aj GdCdYGH GdLeGYjI eKGd JWHjbj aj cQI GdjOs - (3MSf Rcj eMeO eMeO MSfs; (3YeGO GHhGdbGSe eMeO Ydj s ((3GdGScfOQjIs (3GdecJHI GdeUQjI ddWHGYI h GdfTQ h GdJhRjYs, 2004)
(3JfGhd eGgjI GdCdYGH GdLeGYjI h eQcR GdJMce aj GdeLGd GdQjGVj ,ebOeG HYV GdeaGgje h GdBQGA Mhd eQcR GdJMce GdOGNdj h GdNGQLj ,ceG JWQb Edi YQV GdXhGgQ GdSjchdhLjI h GdaSjhdhLjI h YdGbJgG HeQcR GdJMce ,h HYV COhGJ bjGSg,eTjQG dHYV GdOQGSGJ GdYQHjI h GdCLfHjI aj gPG GdeLGd(B.s
Keywords: (3GdCdYGH GdLeGYjI(B_(3JMcjes; (3cQI GdjO (B_(3JMcjes